2009
DOI: 10.1021/bi802294v
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchal Contribution of N- and C-Terminal Sequences to the Differential Localization of Homologous Sodium-Dependent Vitamin C Transporters, SVCT1 and SVCT2, in Epithelial Cells

Abstract: Human sodium-dependent vitamin C transporters, SVCT1 and SVCT2, share 66% sequence identity yet localize in the apical and basolateral membranes of epithelial cells, respectively. This pair thus serves as a model for studying multipass membrane protein targeting. Domain swaps, deletions, insertions, and point mutations were performed on EGFP-tagged hSVCT1 and hSVCT2 plasmids. Mutant proteins stably expressed in MDCK cells were analyzed by confocal microscopy and Transwell ascorbate transport assays. These stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
57
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(68 citation statements)
references
References 39 publications
(99 reference statements)
11
57
0
Order By: Relevance
“…4C). Therefore, these results are consistent with the proposal that both NH 2 -and COOH-terminal sequences act in concert to regulate the cell surface delivery of hSVCT2 (36).…”
Section: Functional Expression Of Hsvct2-yfp In Hepg2 Cellssupporting
confidence: 92%
See 3 more Smart Citations
“…4C). Therefore, these results are consistent with the proposal that both NH 2 -and COOH-terminal sequences act in concert to regulate the cell surface delivery of hSVCT2 (36).…”
Section: Functional Expression Of Hsvct2-yfp In Hepg2 Cellssupporting
confidence: 92%
“…To investigate other molecular determinants that may function in tandem with this COOH-terminal residue, we proceeded to examine the role of the NH 2 -terminal cytoplasmic domain of hSVCT2 (36).…”
Section: Functional Expression Of Hsvct2-yfp In Hepg2 Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…It must be noted that immunouorescence antibodies including anti-SVCT2 and anti-SVCT1 bind SVCTs in a quite different manner from AA or RB-A-Vc, thereby not interfering with the forming of SVCT/RB-A-Vc complexes. 27 Confocal colocalization experiments with anti-SVCT2 and anti-organelle protein markers revealed that most of the SVCT2 immunoreactivity was associated with the mitochondria, with minor colocalization at the endoplasmic reticulum and very low immunoreactivity at the plasma membrane. The transporter SVCT1 is absent from HEK-293T cells.…”
Section: Fluorescence Imaging Of Svcts In the Xed Cellsmentioning
confidence: 97%